O compliance e as repercussões jurídicas no âmbito do direito penal: um estudo sobre a delegação do dever de vigilância envolvendo o dirigente de empresa e o compliance officer - Sardinha, Leonardo Lopes (2024)
The doctoral thesis, which is now presented, has as its starting point an analysis of the risk that permeates contemporary society, marked by technological advances that provide us with comfort and well-being and, at the same time, expose us to risks that even so we had not tried it. Given this, Criminal Law did not appear indifferent to this new reality, trying to adapt to it to become an efficient instrument of defense against the new risks present today, since classical Criminal Law has proven insufficient to protect the society of current dangers. However, this readaptation of Criminal Law to new risks has sparked intense discussions in academia. Normally, business activity brings with it an inherent risk, consisting of the potential for harm to the legal interests of others. This occurs when crimes are committed within the company. That said, compliance emerges as a legal instrument aimed at preventing crimes committed within companies. Thus, compliance is a systematic set of actions adopted in the corporate environment, with the purpose of ensuring that the activities carried out by companies do not violate current legislation. The implementation of the compliance program in companies is a task assigned to the compliance officer. Furthermore, the compliance officer receives, by delegation from the company director, the duty to supervise the functioning of surveillance and control mechanisms, aiming to prevent the occurrence of crimes within the company. In this scenario, there has been debate about the legal consequences, within the scope of Criminal Law, resulting from the delegation of the duty of surveillance involving the company director and the compliance officer. In this sense, the thesis aims to examine the relationship of delegation of the duty of surveillance involving the business manager and the compliance officer, to extract the legal consequences arising from this delegation relationship, from the perspective of Criminal Law. The research method will consist of consulting legislation, national and foreign doctrine, jurisprudential research, academic works, consulting periods, the internet, and databases.